Financial Performance Analysis at PT Bukit Asam, Tbk - Masyadi Masyadi; Sukma Aini; Ilma Ilma (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
This study aims to analyze the financial performance of PT Bukit Asam Tbk, which is one of the State-Owned Enterprises (BUMN) companies engaged in the coal mining sector. PT Bukit Asam Tbk has a strategic role in providing national energy and is an entity that has been listed on the Indonesia Stock Exchange. In this study, a quantitative approach was used with secondary data obtained from the annual financial statements of PT Bukit Asam Tbk during the period 2020 to 2023. Data analysis was carried out descriptively using two main ratios, namely Current Ratio (CR) as an indicator of liquidity, and Return on Assets (ROA) as an indicator of profitability. The results showed that the financial performance of PT Bukit Asam Tbk in terms of liquidity was generally in a healthy condition. Current Ratio during the 2020-2023 period was above the ideal threshold (100%), with an average value of 209.77%. This value reflects that the company has sufficient ability to meet its short-term obligations. However, there was a downward trend in the ratio in 2023 to 151. Meanwhile, in terms of profitability, ROA shows quite fluctuating results, but in general it is in a good category. The average value of ROA over four years is 19.17%, reflecting the company's ability to generate profits from the assets it manages. The year 2022 was the peak of the company's profitability with an ROA of 28.17%. In conclusion, PT Bukit Asam Tbk generally shows healthy financial performance in terms of both liquidity and profitability. However, the downward trend in the last year is an important concern for management in maintaining business stability and sustainability in the future. This research is expected to contribute to investors, academics, and policy makers in understanding the company's financial position and supporting decision making based on appropriate data and analysis.